Enterprise Surveys Follow-up on COVID-19 : What Businesses Experience, Moldova 2021, Round 3 - World Bank Group (World Bank, Washington, DC, 2021)
The outbreak of Coronavirus (COVID-19) affected individuals and businesses, alike. Understanding the impact of the crisis on businesses, and subsequently how firms are recovering, gives insights into the overall health of the economy as the world tackles the health crisis it is facing. The follow-up surveys to the standard Enterprise Surveys (ES) aim to assess how businesses are adapting and recovering as the first signs of improvement appear in the global health situation. This document summarizes the main findings from the third round of follow-up surveys in Moldova.